2020
DOI: 10.1111/1365-2745.13479
|View full text |Cite
|
Sign up to set email alerts
|

A king and vassals' tale: Molecular signatures of clonal integration in Posidonia oceanica under chronic light shortage

Abstract: GO ID GO-Biological process FDR Apical 0080037 negative regulation of cytokinin-activated signalling pathway 3.31E-06 0009737 response to abscisic acid 5.52E-04 0046148 pigment biosynthetic process 1.13E-03 2000762 regulation of phenylpropanoid metabolic process 1.28E-03 0033386 geranylgeranyl diphosphate biosynthetic process 6.78E-03 0006857 oligopeptide transport 9.24E-03 0015698 inorganic anion transport 1.23E-02 0043693 monoterpene biosynthetic process 1.40E-02 0003006 developmental process involved in rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 94 publications
5
25
0
Order By: Relevance
“…There was a trend of a further increase in apical shoots with fertilization at the SB sites, while the opposite trend was observed in seagrasses from NB ( Table 4 ). It has been shown that plants exposed to stressors have a higher number of apical shoots in their shoot population to secure the persistence of their population ( Ruocco et al, 2020 ). In this way, seagrasses are able to spread and find more favorable habitats ( Meinesz and Lefevre, 1984 ; Ruocco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a trend of a further increase in apical shoots with fertilization at the SB sites, while the opposite trend was observed in seagrasses from NB ( Table 4 ). It has been shown that plants exposed to stressors have a higher number of apical shoots in their shoot population to secure the persistence of their population ( Ruocco et al, 2020 ). In this way, seagrasses are able to spread and find more favorable habitats ( Meinesz and Lefevre, 1984 ; Ruocco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that plants exposed to stressors have a higher number of apical shoots in their shoot population to secure the persistence of their population ( Ruocco et al, 2020 ). In this way, seagrasses are able to spread and find more favorable habitats ( Meinesz and Lefevre, 1984 ; Ruocco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plants try to spread horizontally to recover and find more favorable conditions ( Meinesz and Lefevre, 1984 ). Indeed, stressed meadows will prioritize apical shoots survival in order to secure population persistence and spread to more favorable habitats ( Ruocco et al, 2020 ). In order to respond to temperature stress, plants can perform escape strategies other than favoring the growth of apical shoots, and can invest resources in flowering, seeking for spreading through sexual reproduction ( Ruiz et al, 2018 ; Marín-Guirao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results, cytosine methylation increased more in heat-sensitive genotypes of Brassica napus under increased temperatures than in heat-tolerant genotypes, likely to respond and adapt to heat-stress 80 . In seagrasses, global DNA hyper-methylation and methylation changes in target functional genes of P. oceanica have been shown under increased cadmium levels and reduced light conditions 56,57,60 , and have been proposed to be at the basis of the species acclimation to heat stress 54,58 . P. oceanica cold-plants not only changed DNA methylation levels during the warming exposure, but they also showed the modulation of genes involved in epigenetic processes commonly used by plants for the transcriptional stimulation of stress tolerance and flowering as a possible mechanism to survive and optimize reproductive success under stress conditions 85 .…”
Section: Cold-plants W Arm-plants Cold-plants W Arm-plantsmentioning
confidence: 99%